2005
DOI: 10.1074/jbc.m505524200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin Induces Heat Shock Protein 70 and Protects against MPTP-induced Dopaminergic Neurotoxicity in Mice

Abstract: As key molecular chaperone proteins, heat shock proteins (HSPs) represent an important cellular protective mechanism against neuronal cell death in various models of neurological disorders. In this study, we investigated the effect as well as the molecular mechanism of geldanamycin (GA), an inhibitor of Hsp90, on 1-methyl-4-pheny-1,2,3,6-tetrahydropyridine (MPTP)-induced dopaminergic neurotoxicity, a mouse model of Parkinson disease. Neurochemical analysis showed that pretreatment with GA (via intracerebral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 55 publications
(103 reference statements)
8
118
0
Order By: Relevance
“…Several experiments using administration of GA in vitro have indicated its neuroprotective activity via preventing α-synuclein aggregation and neurotoxicity and protecting dopaminergic neuron death (McLean et al 2004;Shen et al 2005). In the terms of AD studies, GA has been shown to promote the binding of tau protein to microtubules, leading to a significant reduction in tau aggregation (Dou et al 2003), although its action on Aβ-mediated apoptosis and oxidative stress has not been yet studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments using administration of GA in vitro have indicated its neuroprotective activity via preventing α-synuclein aggregation and neurotoxicity and protecting dopaminergic neuron death (McLean et al 2004;Shen et al 2005). In the terms of AD studies, GA has been shown to promote the binding of tau protein to microtubules, leading to a significant reduction in tau aggregation (Dou et al 2003), although its action on Aβ-mediated apoptosis and oxidative stress has not been yet studied.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein (HSP) 90 is implicated in maintaining the conformation, stability, and function of key proteins involved in signal transduction pathways (3), and we therefore hypothesized that HSP90 inhibitors [geldanamycin, 17-allylamino-17-demethoxygeldanamycin (17-AAG), and 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (NSC 707545, 17-DMAG)] would potentiate the effect of ATO on constitutive STAT3 activity in AML cells. One concern was that up-regulation of HSP70, a protein known to inhibit apoptosis (4,5), by exposure to either ATO (6 -8) or HSP90 inhibitors (9,10), might abrogate their effect on constitutive STAT3 activity and survival.…”
mentioning
confidence: 99%
“…Genetic studies in Drosophila showed that the overexpression of Hsp70 suppressed polyglutamine-induced neurodegeneration in vivo (22). Shen et al reported that the induction of Hsp70 is critical to the neuroprotection afforded by geldanamycin against MPTP-induced neurotoxicity in the mouse brain (23). Moreover, induction of Hsp70 by prior exposure to heat shock protects against MPP + -induced neuronal cell death in cultured PC12 cells (11) and against α-synuclein aggregation in human H4 neuroglioma cells (7,8).…”
Section: Discussionmentioning
confidence: 99%